2017
DOI: 10.1186/s12978-017-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

PRENACEL – a mHealth messaging system to complement antenatal care: a cluster randomized trial

Abstract: BackgroundThe aim of this study was to determine whether PRENACEL (a bi-directional, mobile-phone based, short text message service (SMS)) increases the coverage of recommended antenatal care (ANC) practices.MethodsA parallel, cluster-randomized trial in which 20 public primary Health Care Units (PHCUs) were randomly allocated to the intervention (10 PHCUs) or control (10 PHCUs) group. The study population included pregnant women aged 18 or above with a gestational age of 20 weeks or less. Pregnant women recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
11

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 21 publications
1
60
0
11
Order By: Relevance
“…Most tellingly related to asthma and pregnancy and for our study, although many studies relating to asthma and mHealth have been conducted with adolescents rather than adults, one systematic review indicated that mobile technology could improve adherence with asthma medications and was beneficial for self‐management (Miller, Schüz, Walters, & Walters, ). mHealth has beneficial impacts on self‐management in general lifestyle factors associated with pregnancy, according to some primary research studies (Naughton et al., ; Oliveira‐Ciabati et al., ; Van Dijk et al., ) and reducing hospital admissions in those with more severe asthma (McLean et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most tellingly related to asthma and pregnancy and for our study, although many studies relating to asthma and mHealth have been conducted with adolescents rather than adults, one systematic review indicated that mobile technology could improve adherence with asthma medications and was beneficial for self‐management (Miller, Schüz, Walters, & Walters, ). mHealth has beneficial impacts on self‐management in general lifestyle factors associated with pregnancy, according to some primary research studies (Naughton et al., ; Oliveira‐Ciabati et al., ; Van Dijk et al., ) and reducing hospital admissions in those with more severe asthma (McLean et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This study was registered at the Brazilian Clinical Trials Registry (REBEC, registration number RBR-54zf73, available at http:// ensaiosclinicos.gov.br/rg/RBR-54zf73/. The component for pregnant women was published in 2017 and 2019 [39,40].…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…In the first stage, two groups (with ten units each one) were randomly selected, balanced considering the size of the affiliated population and the vulnerability situation (evaluated by the number of beneficiaries of the government welfare program) of each health unit. Groups were balanced when the difference between population size and vulnerability was less than 15% stipulated by some criteria [39]. For the randomization, Microsoft Excel 2013 was used.…”
Section: Randomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study aims to discuss the process of developing and evaluating messages sent via SMS to the partners of pregnant women with a view to engaging them in the pregnancy-puerperal period and encouraging the acceptability of this content. These messages were prepared in the context of PRENACEL (Prenatal in the Cell Phone), which developed a bidirectional communication channel by sending short text messages (SMS) to the cell phone, addressing the Brazilian reality of pregnant women and partners using the National Health System (SUS) in a municipality in the state of São Paulo, providing information, receiving complaints and grievances, clarifying doubts and stimulating the engagement and demand for effective interventions during prenatal, delivery and the puerperium period 18 .…”
Section: Introductionmentioning
confidence: 99%